(untitled) - Enrico Cillari (Hà Nội, 1997)
The book contains many units. Each of them begins with a dialogue and some practical activities which will prepare to communicate not only with other members of the medical profession but with also with their patents
Keywords: english language - medical english,medicine - terminology